The Effect Of Working Capital Turnover And Debt Policy On The Value Of Technology Companies Listed On The Indonesia Stock Exchange (IDX) In 2020-2024 - Siti Nurersyah Midar (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The technology sector is a key driver of digital economic growth in Indonesia. However, during the 2020–2024 period, several companies in this sector experienced stock price volatility, indicating pressure on company value. This issue prompted this study, which aims to analyze the effect of working capital turnover and debt policy on company value in technology sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This study used a quantitative approach with a panel data regression method, and the sample was determined through purposive sampling technique, involving 10 companies that met the criteria for data availability over five years of observation. The results showed that working capital turnover had a negative but insignificant effect on company value, while debt policy had a negative but significant effect on company value. This finding supports the Trade-off Theory, which emphasizes the existence of an optimal point for debt use, but is inconsistent with Agency Theory's expectations regarding efficient working capital management as a means of increasing value. This study concludes that increasing the proportion of debt has the potential to reduce company value due to increased financial risk, while efficient working capital turnover has not been able to provide a significant impact. Therefore, companies need to consider balancing their funding structure and improving the quality of current asset management to strengthen market perception and increase company value sustainably.